Cellular expression of CD markers in immune thrombocytopenic purpura: implications for prognosis. Issue 6 (20th June 2018) - Behzad, Masumeh Maleki; Asnafi, Ali Amin; Jalalifar, Mohammad Ali; Moghtadaei, Mostafa; Jaseb, Kaveh; Saki, Najmaldin
Abstract : Immune thrombocytopenic purpura (ITP) is an autoimmune bleeding disorder associated with platelet destruction. Abnormalities in frequency and function of different immune cells can play a crucial role in this disease. The aim of this study was to evaluate the prognostic value of CD markers' expressions by immune cells in ITP. Peripheral blood samples were collected from 25 ITP patients before and after treatment. The expression of CD markers was evaluated by flow cytometry technique. The expression of CD38 and CD56 was significantly lower before treatment than after it (p = 0.025 and p = 0.036, respectively). Furthermore, a positive correlation was found between CD38 expression with platelet count before (r = 0.496, p = 0.012) and after treatment (r = 0.404, p = 0.045). No significant relationship was found between this marker and platelet count while CD4 expression was higher before treatment than after it (p = 0.002). In conclusion, CD38 may have independent prognostic value in ITP and we suggest that it can be a prognostic marker for this disease.